Regional and racial disparity in proximal gastric cancer survival outcomes 1996–2016: Results from SEER and China National Cancer Center database - Zhao, Lulu (Cancer Med, 2021)
BACKGROUND: Given the growing incidence and aggressive biological behavior of proximal gastric cancer (PGC) as reported, it is important to understand which regional or racial populations are at poor prognosis so that interventions can be treated appropriately. We sought to explore regional treatment differences as well as racial genes influence survival outcomes in China and the US patients with PGC. METHODS: PGC patients defined as tumors with the epicenter located in cardia (C16.0) or fundus (C16.1) from 1996 to 2016 were identified from the Surveillance Epidemiology and End Results (SEER) in the United States as well as data from a high‐volume National Cancer Center Database in China. Overall survival (OS) curves were plotted for different regional or racial groups, respectively, using the Kaplan‐Meier method and compared statistically using the log‐rank test. Differentially expressed genes (DEGs) analysis was performed using TCGA database. RESULTS: Finally, the cohort consistent of 40973 PGC patients who enrolled in SEER database (n = 36305) or China National Cancer Center (n = 4668), and divided into 4 racial groups: Chinese (n = 5179), Black (n = 2429), White (n = 31185), and Others (n = 2096). After controlling for confounding variables, racial factors were independently associated with poor survival included Black ethnicity (HR = 1.376, 95% CI: 1.066–1.7760, p = 0.014) and White ethnicity (HR = 1.262, 95% CI: 1.005–1.583, p = 0.045) when compared to Chinese ethnicity in total PGC patients. Even in the same region for only US group, Chinese PGC patients also showed better prognosis. CONCLUSIONS: In conclusion, we demonstrated the different survival outcomes of PGC patients in different regions or races from two high‐volume database SEER and China National Cancer Center database. These survival differences are likely influenced by a number of factors (e.g., access to screening, quality of gastrectomy, neo/adjuvant therapy, and biological genes itself). More importantly, a better understanding of these disparities could lead to interventions that may help to abolish these disparities.